2019
DOI: 10.1016/j.gca.2018.09.034
|View full text |Cite
|
Sign up to set email alerts
|

Temporal deconvolution of vascular plant-derived fatty acids exported from terrestrial watersheds

Abstract: Relatively little is known about the amount of time that lapses between the photosynthetic fixation of carbon by vascular land plants and its incorporation into the marine sedimentary record, yet the dynamics of terrestrial carbon sequestration have important implications for the carbon cycle. Vascular plant carbon may encounter multiple potential intermediate storage pools and transport trajectories, and the age of vascular plant carbon accumulating in marine sediments will reflect these different pre-deposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 104 publications
1
29
0
Order By: Relevance
“…This offset between both biomarker 14 C ages and catchment-weighted soil 14 C ages on one hand and τ soil on the other hand likely reflects the fundamental principles governing organic matter degradation and aging. Natural organic matter is compositionally heterogenous, with age heterogeneity evident even within individual compound populations ( 20 , 35 ). Complex interplay between environmental properties and chemical composition results in widely variable OC degradation rates ( 36 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This offset between both biomarker 14 C ages and catchment-weighted soil 14 C ages on one hand and τ soil on the other hand likely reflects the fundamental principles governing organic matter degradation and aging. Natural organic matter is compositionally heterogenous, with age heterogeneity evident even within individual compound populations ( 20 , 35 ). Complex interplay between environmental properties and chemical composition results in widely variable OC degradation rates ( 36 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recently synthesized biospheric carbon then transmits this bomb 14 C signal through river basins, inducing time-variable deviations from natural 14 C levels. We have examined this potential influence on observed signals for selected river systems in two different ways: 1) through comparison of data from samples from the same river system but collected at different times over the last few decades; and 2) through analysis of rapidly accumulating and well-dated fluvially influenced sedimentary sequences with well-defined chronologies that span a time interval encompassing the bomb spike ( 20 , 35 ). Although the influence of the bomb 14 C spike clearly manifests itself in plant-wax fatty acids, the induced variability is small relative to the overall 14 C variability observed within the global dataset presented in this study.…”
Section: Methodsmentioning
confidence: 99%
“…These biomarkers, and associated techniques, have identified that land-based organic material is sometimes a major contributor to marine particulate organic matter flux. While many of these and other tracer studies confirm the terrigenous origin of particulate organic matter and sediments, they do not identify the specific catchment sources unless a single major river inflow is in proximity (Vonk et al, 2019).…”
Section: Introductionmentioning
confidence: 85%
“…The IIIa/IIa ratio (Xiao et al, 2016;Martin et al, 2019) is 1.6 ± 0.4 for UD-4, 1.5 ± 0.2 for MD-2 and 1.4 ± 0.3 for MD-1, which also points toward a lacustrine in situ production (the reported threshold is > 0.9 for in situ aquatic production, in one soil of the Mackenzie region it is 1.2, Peterse et al, 2014). The Mackenzie River transports large quantities of soil-derived organic matter (Vonk et al, 2019), and is therefore a potential source of soil-derived brGDGTs, especially to the no-closure lakes. However, the distribution of brGDGTs in Mackenzie River SPM differs from that in lakes with IIa (IIa + IIa') and IIIa (IIIa = 15% and IIIa' = 19%) as main brGDGTs (34% each, Peterse et al, 2014) and IIIa/IIa equal to 1.0 ± 0.1 (n = 6; Peterse et al, 2014).…”
Section: Provenance Of Brgdgt Lipidsmentioning
confidence: 81%